Internalization Values of Islamic Education at University - Parhan, Muhamad; Faiz, Aiman; Karim, Abdul; Nugraha, Risris Hari; Subakti, Ganjar Eka; Islamy, Mohammad Rindu Fajar; Budiyanti, Nurti; Fuadin, Ahmad; Tantowi, Yusuf Ali (International Journal of Psychosocial Rehabilitation, 2026)
–Islamic education learning in university is not only deducing the end result of human intelligence and human skills, which does not necessarily produce intelligent humans and skilled humans. This means that learning is not only limited to the transfer of knowledge, but at the same time transform of value and transform of attitude by discovering the essential values behind theoretical subject matter. Learning is done in depth (deep learning) and comprehensive, by exploring the values of meaningfulness in each subject matter delivered, through the stages: Receiving, awareness, responding, valuing, organization, and characterization with the process: moral information level, moral belief level, moral attitude level, moral value level, moral character/personality level, and moral dignity level.